The Determinants of Capital Structure: Based on Empirical Evidence from Indian Firms - Jain, Jivansh (2022)
This dissertation is a research on the capital structure choices of the firms in India. It analyses the relationship of six determinants – profitability, firm size, asset tangibility, non-debt tax shields, growth, and financial distress (volatility) – with the book value of total, long-term, and short-term leverage. The sample data for the analysis consists of 175 listed Indian companies, largest in the country by their market capital. A cross-sectional study is conducted with a multiple linear regression analysis. The research studies the existing literature and applies the two most widely accepted theories (trade-off and pecking order) to the results. The study finds out that for Indian firms, long-term leverage is based on the company's financing decisions and is significantly affected by the chosen determinants (except growth and volatility). In contrast, short-term leverage is more transactional in nature, considering that not a single determinant had a significant statistical impact or explanatory power on short-term leverage. Moreover, profitability and non-debts tax shield were found to be negatively related to total leverage and long-term leverage, and size and asset tangibility were found to be positively related with total and long-term leverage. From the theory point of view, neither of the two theories can explain the relationship of all the variables. Pecking order theory dominates when it comes to explaining the negative relationship of leverage with profitability. However, trade-off theory explains the relationships of firm size and non-debt tax shields with leverage. Pecking order theory does explain the positive relationship of growth, but the analysis shows that it is statistically insignificant. Trade-off theory explains just one more variable than pecking order theory, so it can be concluded that trade-off theory fairs a little better than pecking order but does not entirely explain the capital structure choices of Indian firms